Diving Beyond Dollars – Unravelling The Dynamics of De Dollarization (British Journal of Multidisciplinary and Advanced Studies, 2024)
In an intricate dance of global finance, the concept of de-dollarization emerges as a pivotal narrative, underscored by both promise and complexity. While efforts to lessen reliance on the US Dollar intensify, its hegemonic grip remains formidable, fortified by its stable financial markets. The unfolding discourse spotlights the imperative of diversification, navigating trade disparities, geopolitical influences, and the quest for fiscal sovereignty. Amidst this backdrop, India, a burgeoning economic force, contemplates its role in this paradigm shift. However, the trajectory of de-dollarization is no swift panacea, but a nuanced recalibration. It hinges on a multipolar vision yet grapples with challenges of identifying alternative currencies, managing high debt, and steering through periods of potential volatility. As the global community collectively seeks equilibrium, the pursuit of de-dollarization signals a shared aspiration toward a more balanced and inclusive global economic realm.